The Effects of Relaxing Music on Life Distress and Maternal-fetal Attachment in Pregnant Women - Mona Shokri Shams; Anahita Khodabakhshi-Koolaee; Mohammad Reza Falsafinejad (Iran University of Medical Sciences, 2021)
Background: Although pregnancy and motherhood are enjoyable experiences, they are associated with numerous biopsychological changes requiring adaptation. The present study aimed to assess the effects of relaxing music on life distress and Maternal-Fetal Attachment (MFA) in pregnant women. Methods: This was a quasi-experimental study with a pre-test, post-test and a control group design. The research population included all Iranian pregnant women referring to Laleh Hospital in Tehran City, Iran, in 2020. In total, 30 women were selected using the convenience sampling method and randomly assigned into the intervention and control groups (n=15/group). The required data were collected using the Life Distress Inventory (LDI) and the Maternal-Fetal Attachment Scale (MFAS). The intervention group listened to relaxing music for twelve 45-50-minute sessions in the morning and during routine midwifery visits; however, the controls received no intervention. The collected data were analyzed using Multivariate Analysis of Covariance (MANCOVA) in SPSS V. 22. Results: The obtained results indicated that the intervention group reported a lower level of life distress in the post-test, compared to the controls (P=0.0001, F=15.860). The intervention group also achieved a higher mean score on MFA, than the control group (P=0.0001, F=35.872).  Conclusion: According to the present research findings, reproductive health, nursing professionals, and psychologists could recommend music as a complementary therapy to reduce stress and distress experienced by expecting mothers and to improve MFA.